1997
DOI: 10.1128/mcb.17.12.6887
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recognition of Liganded and Unliganded Thyroid Hormone Receptor by Retinoid X Receptor Regulates Transcriptional Repression

Abstract: Thyroid hormone receptor (TR) functions as part of multiprotein complexes that also include retinoid X receptor (RXR) and transcriptional coregulators. We have found that both the TR CoR box and ninth heptad are required for RXR interaction and in turn for interaction with corepressor proteins N-CoR and SMRT. Remarkably, the recruitment of RXR to repression-defective CoR box and ninth-heptad mutants via a heterologous dimerization interface restores both corepressor interaction and repression. The addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 48 publications
4
35
0
1
Order By: Relevance
“…Interestingly, a study by Zhang et al showed that the Gal4 fusion with a TR hinge mutant fails to repress (54), a result also consistent with the notion that the hinge region mutation leads to a structural alteration in the LBD (42). However, cotransfection of Gal4-RXR restores the repression function of the mutant TR, although Gal4-RXR alone does not lead to repression (54). This finding was interpreted in a model in which efficient corepressor binding engages surfaces contributed by both TR and RXR (54).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly, a study by Zhang et al showed that the Gal4 fusion with a TR hinge mutant fails to repress (54), a result also consistent with the notion that the hinge region mutation leads to a structural alteration in the LBD (42). However, cotransfection of Gal4-RXR restores the repression function of the mutant TR, although Gal4-RXR alone does not lead to repression (54). This finding was interpreted in a model in which efficient corepressor binding engages surfaces contributed by both TR and RXR (54).…”
Section: Discussionsupporting
confidence: 55%
“…1C). The notion that the apo-RXR LBD does not associate tightly with the inhibitor/corepressor is supported by the findings that a Gal4-RXR LBD fusion mediates little repression (43,54) and that a Gal4-RXR (LBD)-VP16 chimera is constitutively active (43).…”
Section: Activation Of Gtv By Liganded Rxr Lbdsupporting
confidence: 52%
“…Many nuclear receptors require heterodimerization with RXR for high-affinity DNA binding, and this receptor appears to play an active role in corepressor interaction (49). It has been proposed that sequence-specific interactions between H12 of RXR and a hydrophobic cleft of unliganded TR formed by residues in H3, H4, and H5 reposition H12 and unmask the corepressor interaction surface of RXR, allowing the unoccupied TR/RXR heterodimer to repress transcription.…”
mentioning
confidence: 99%
“…The stronger silencing potency of F451X was believed to be, at least in part, due to its increased ability to interact with RXR and SMRT. It has been reported that RXR potentiates and stabilizes TR-co-repressor interaction in solution (Zhang et al 1997). However, F451X did not increase the ability of TR to associate with N-CoR, despite the enhanced heterodimerization with RXR ( Fig.…”
Section: Discussionmentioning
confidence: 88%